UPAYA MENINGKATKAN MINAT BACA SEBAGAI SARANA UNTUK MENCERDASKAN BANGSA - Kasiyun, Suharmono (Universitas Negeri Surabaya, 2015)
This study aims to find laternatif way to improve society’s reading prolicity, particularly for school members, as a solution to overcome the low of reading. The reading prolicity has a great influence to the progress of the nation-state. Compare to the neighbor country, Indonesian reading prolicity is still low. It is a key to boost the progress because the capability of science and technology can be achieved through reading skills. Family, society, and educational institution have significant role in improving reading skills. It is responsible for all elements of society like librarian, teachers, parents, and society itselves. Librarian and teachers have direct responsible in improving that. To deal with that, it is good to give stimulant in gaining the reading tradition. The reading force is not effective for students. It is also unrecognized to force student to buy books.